PENGARUH MOBILISASI CHEST TERHADAP PENINGKATAN EKSPANSI THORAKS PADA PENYAKIT PARU OBSTRUKTIF KRONIS DI BALAI BESAR KESEHATAN PARU MASYARAKAT MAKASSAR - Hafsah Tahir; Sitti Muthiah; Muhammad Awal (Media Fisioterapi Politeknik Kesehatan Makassar, 2021)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a chronic disease characterized by productive cough, dyspnea and airway obstruction even though this disease is chronic and is a combination of emphysema, chronic bronchitis and asthma, but in certain circumstances worsening of respiratory function occurs . In some circumstances, the worsening of COPD can lead to respiratory failure.Methods: This research is a pre-experimental study with a one group pretest-posttest research design using a purposive sampling technique, which aims to determine an increase in thoracic expansion in patients with chronic obstructive pulmonary disease, with a population of 16 people, a total sample of 15 people is obtained based on the sample size formula and meeting the inclusion criteria, each sample was given chest mobilization treatment.Results: The results showed that the average value of thoracic expansion before treatment was at the axilla point = 0.53, costa point 4-5 = 2.33 and point proc. xyphoideus = 4.47 using a measuring instrument, namely a measuring tape. Statistical results using the Wilcoxon test show that the p value for thoracic expansion at each point is p = 0.000 which is less than α = 0.05 (p<α) which means the working hypothesis is accepted.Conclusion: The conclusion of this study is by giving chest mobilization for 8 treatments can produce a significant effect on changes in thoracic expansion in patients with chronic obstructive pulmonary disease, in other words giving chest mobilization is more effective in increasing thoracic expansion in patients with chronic obstructive pulmonary disease. Keywords: Chest mobilization, chronic obstructive pulmonary disease, thoracic expansion